The compliance of basel convention 1989 in reference to scheduled waste management in Malaysia / Raja Muhammad Yusufi Raja Hairuanuar ...[et al.] - Raja Hairuanuar, Raja Muhammad Yusufi; Zaharuddin, Nur Hidayah; Houd, Nursyamimi; Mohd Sanusi, Siti Syazana (2010)
In this research paper, we are discussing on the topic of the compliance of the scheduled waste management in Malaysia with reference to the Basel convention 1989. The main issues regarding this particular topic is about the transboundary movement of scheduled waste management. We referred to the main governmental bodies that are responsible in terms of scheduled waste and we also tackled the issue of compliance with the Basel Convention 1898. This research paper will focus on the issue of compliance by Malaysia to the Basel Convention 1989 as Malaysia has been part of this international treaty for more then a decade. We shall see on what aspects Malaysia has complied with the Basel Convention and what has been improved by making the Basel Convention as a reference to Malaysia local laws. At the end of this research, we know that the level of compliance to the Basel Convention in Malaysia is high as lots of steps have been taken by the governmental bodies to supervised and make sure the obligations are fulfilled. The main compliance that can be clearly seen is by having the scheduled wastes regulations that is being used in Malaysia and also the strict requirements needed in order to export and import the scheduled wastes.